Effects of late rotation fertilization and nutrient cycling on pine plantation productivity in the Mpumalanga Province of South Africa - Odiwe, Anthony Ifechukwude (My University, 2010)
The southern African forestry and forest products industry is an important part of the southern African economy and there is the need to increase and improve plantation productivity to meet both domestic and external needs. Fertilizer applications have been widely used to increase productivity and there has been increasing interest in late rotation fertilization applications. This study evaluated the impact of late rotation fertilization on soil properties and biologically based processes in Pinus patula and Pinus elliottii species in order to increase the understanding of nutrient cycling and impact on tree growth. The 3-PG and Nitrogen (N) mineralization model were used to improve the predictive understanding of the system. The late rotation fertilization trial established in 11-year-old P. patula plantations in 2001 and a new late rotation fertilization trial in a 17-year-old P. elliottii plantation established in 2006 in the Mpumalanga province, South Africa were sampled. Six existing fertilizer treatments in four P. patula sites, with two, replicates were used, whereas four treatments with four replicates were sampled at the P. elliottii site. The treatments in P. patula were 100 kg ha-1 N fertilizer applied in various combinations of limestone ammonium nitrate (LAN) and urea in 2001 and 2003; while in P. elliottii, 200 kg ha-1 N as LAN and 100 kg ha-1 phosphorus (P) as Super Phosphate was applied in 2006. Soil properties were analyzed in 2006 and 2007; litter fall, litter decomposition, litter accumulation and N mmineralization rates were determined from May 2006 to May 2007; foliar sampling and litter accumulation and nutrient concentrations were also determined. The outputs of the 3-PG model, quadratic mean diameter at breast height, basal area and stand volume, were compared with the field measurements. Late rotation fertilization generally had no significant effects on the measured tree growth parameters, soil properties and other biological process for either of the two species. These findings indicate that the sites are not nutrient limited. Tree growth, litter fall, litter accumulation and nitrogen mineralization rates differed significantly across the P. patula sites. Large amounts of N and P were found in the forest floor litter with P. patula having 293-614 kg ha-1 and 14-36 kg P ha-1 and P. elliottii 94-150 kg N ha-1 and 5-11 kg P ha-1. High foliar Calcium:Nitrogen (17-42) and Potassium:Nitrogen (29-48) ratios can be used as indicators of nutrient availability at the sites and possibly as indicators of response to fertilization. Climatic factors, especially the limited rainfall amount and its variable distribution, played a confounding role in understanding the response to the late rotation fertilizer applications. Tree growth parameters were well predicted with the 3-PG model, high correlations for quadratic mean DBH (r = 0.99), stand volume (r = 0.95-0.99) and basal area (r = 0.080-0.98) were found for all of the P. patula sites, except at the Elandshoogte site, where basal area was poorly predicted. The tree growth parameters at the P. elliottii site were well predicted, with 2-10% deviation, for 2006 and 2007. Deviations in the longer term (2017) were much larger (23%). The systems based approach to nutrient cycling and the two models used in this study were valuable in understanding the response to late rotation fertilization. These approaches pointed to key processes e.g. forest floor litter accumulation, nutrient concentrations and decomposition rates; foliar nutrient ratios, which need careful monitoring and management to facilitate high nutrient turnover. Late rotation fertilization should only be used as a management practice in areas with soil nutrient limitation and where rainfall is high with a reliable distribution. Sustainable plantation productivity continues to be a challenge especially in South Africa and will become worse as the global financial crisis deepens and the climate variability increases.